Analysis of risk factors and establishment of prediction model for lower extremity deep vein thrombosis after lumbar fusion surgery - Yixiang Zhao; Xiangzhen Kong; Kangle Song; Zhenchuan Liu; Yuanqiang Zhang; Lei Cheng (BMC Surgery)
Abstract Background Lower extremity deep vein thrombosis (LEDVT) is a common complication after orthopedic surgery. Currently, a reliable assessment tool is lacking to evaluate the risk of postoperative LEDVT in patients undergoing lumbar fusion surgery. This study aims to explore the risk factors for LEDVT formation after lumbar fusion surgery and establish a predictive model for it. Methods Data of patients admitted for multi-center spinal surgery from May 2022 to September 2023 were retrospectively collected. Patients were divided into DVT and non-DVT groups based on the occurrence of LEDVT after surgery. Potential risk factors were initially identified through intergroup comparative analysis and single-factor logistic regression, which were considered candidate indicators. LASSO regression was applied to select candidate indicators, and the filtered variables were included in a multivariable logistic regression model. Nomogram and dynamic nomogram were constructed to visualize the model, and the model was subsequently validated. Results Factors including weakened lower extremity muscle strength, intraoperative blood loss, walking impairment, and Venous reflux/ Varicose veins were included in the multivariable logistic regression model. The results showed that the model had an area under the receiver operating characteristic curve of 0.870, 0.777 and 0.750 for the training set, internal validation set, and external validation set, respectively. Nomograms and web-based dynamic nomograms were created based on the multivariable logistic regression model. The model exhibited good performance in calibration curves and decision analysis. Conclusion The study identified weakened lower extremity muscle strength, intraoperative blood loss, walking impairment, and Venous reflux/ Varicose veins as risk factors for LEDVT formation following lumbar fusion surgery. The predictive tool established based on the logistic regression model demonstrated good performance and can be considered for assessing the risk of LEDVT formation after lumbar fusion surgery.